Análise da competitividade da cadeia produtiva da soja no continente africano: Moçambique, uma nova fronteira agrícola - Janeque, Ricardina António (2019)
Studying the market and competitiveness of soybeans in Mozambique assumes greater importance for a wide range of social, political, economic and technological aspects. Therefore, the objective was to analyze the technical-socio-political and economic conditions of the soybean production chain in the main producing regions of Mozambique and their prospects for consolidation. For this, it was based on theories of analysis of productive chains and theory of the systemic competitiveness. The data used were primary and secondary. The primary was obtained through field research with soybean farmers, input suppliers and soybean processing industries in the districts of Ribáuè, Maleuma, Gurué, Namarroe, Alto Molócuè, Sussundenga, Bárue, Macate, District of Manica, Tsangano and Angónia, in which were semi-structured questionnaires from January to March of 2018. The sample was made up of 124 soybean farmers, selected from the "snowball" sampling technique, three input suppliers and two processing industries. Secondary data were obtained from FAOSTAT and TechnoServe. Statistical techniques were used to compile and process data. Descriptive statistics (frequency distribution and measures of central tendency) and multivariate statistics (Exploratory Factor Analysis and Conglomerate Analysis) were used. The results showed that on the African continent as well as in Mozambique, soybean cultivation is growing and growing, with yields still low in most countries, also in Mozambique. On the other hand, soybean producers interviewed showed that they are in the initial phase of knowledge of the crop, with low control of soybean production processes, input suppliers characterized by commercialization of inputs considered basic not involving agricultural machinery and the processing industries are still processing small amounts of soybeans due to the low grain supply in the country. In the production segment, the methanol showed that there is a weak coordination among the agents of the chain, which translates into low and low levels of technical assistance obtained by soybeans, low use of technological packages, low productivity, low level of technological training , lack of contracts with other entities and lack of financing, demonstrated by the micro and mesonível. However, the deficient supply of agricultural inputs directly influences their use in soybean production, providing low yields, low amounts of soybeans on the market, and this also impacts the functioning of the processing industries, which produce less than they are capable of and supply needs. This shows that there is a need for intensification of public and private policies so that there is more interaction and organization on the part of the actors of the chain, and thus, to consolidate the soybean activity to obtain competitive gains. The overall conclusion of the research is that the soybean production chain is at an initial level of development, but there are conditions for its development and consolidation in the coming years.